Surgical outcomes of laparoscopic cholecystectomy in scleroatrophic gallbladders - Musa AKOĞLU,; Metin ERCAN,; E. Birol BOSTANCI,; Zafer TEKE,; Erkan PARLAK, (Turkish Journal of Gastroenterology, 2019)
-